2014
DOI: 10.1542/peds.2013-3524
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Abstinence Syndrome

Abstract: Neonatal abstinence syndrome (NAS) is a result of the sudden discontinuation of fetal exposure to substances that were used or abused by the mother during pregnancy. Withdrawal from licit or illicit substances is becoming more common among neonates in both developed and developing countries. NAS continues to be an important clinical entity throughout much of the world. NAS leads to a constellation of signs and symptoms involving multiple systems. The pathophysiology of NAS is not completely understood. Urine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
480
0
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(504 citation statements)
references
References 164 publications
(157 reference statements)
6
480
0
18
Order By: Relevance
“…However in some other studies up to 90% of the neonates were reported to require pharmacologic treatment for NAS (7,20). The treatment rate varies depending on the type of drugs abused by mothers; the requirement for pharmacologic treatment is usually higher among poly substance and opioid exposed neonates while it is lower in stimulants only exposed neonates whose the majority do not require pharmacologic treatment (7,18).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However in some other studies up to 90% of the neonates were reported to require pharmacologic treatment for NAS (7,20). The treatment rate varies depending on the type of drugs abused by mothers; the requirement for pharmacologic treatment is usually higher among poly substance and opioid exposed neonates while it is lower in stimulants only exposed neonates whose the majority do not require pharmacologic treatment (7,18).…”
Section: Discussionmentioning
confidence: 98%
“…Based on a recent report of national survey on drug use and health (NSDUH) in the United States 5.9% of pregnant women are using illicit drugs during gestation (6). Among the neonates who were exposed to illicit drugs in utero, withdrawal signs and symptoms requiring medical intervention develop in 27% -91% (7).…”
Section: Introductionmentioning
confidence: 99%
“…2,6 Increases in the incidence of NAS have been reported uniformly in community hospitals, teaching hospitals, and children's hospitals, have affected all racial and ethnic groups, and have been described both nationally and internationally. [7][8][9][10] Variations in NAS treatment and associated outcomes persist in the absence of a nationally accepted, evidencebased, and generalizable treatment protocol. [11][12][13] The average length of hospitalization among infants treated for NAS is ∼16 days (23 days for infants receiving pharmacologic treatment of NAS), although longer stays are common.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Substance use during pregnancy can affect the foetus both directly passing through placental barrier and indirectly through poor maternal health habits and environmental conditions [3,4].…”
Section: Introductionmentioning
confidence: 99%